The perils of personalism. Issue 2 (17th February 2020) - Rhodes-Purdy, Matthew; Madrid, Raúl L.
ABSTRACT: What impact does personalism, or presidential dominance of a weakly organized ruling party, have on the level of democracy? We argue that presidents who dominate their own weakly organized parties are more likely to seek to concentrate power, undermine horizontal accountability, and trample the rule of law than presidents who preside over parties that have an independent leadership and an institutionalized bureaucracy. Independent party leaders, we suggest, will often try to curb the excesses of the president in order to protect their own political prospects. We explore these hypotheses through a quantitative analysis of the determinants of the level of democracy in 18 Latin American countries from 1980–2015. We find that personalism has a consistently negative impact on the level of democracy in Latin America.